PENGARUH PENGGUNAAN E-MODUL MATEMATIKA BERBASIS CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN KEMAMPUAN LITERASI NUMERASI PESERTA DIDIK KELAS X SMKN 1 SIJUNJUNG - Anwar, Fahrezi (Departemen Matematika, 2024)
Improving their numerical literacy is one of the goals that the pupils are working towards. However, this is still an area where the students in SMKN 1 Sijunjung's class X fall short. This problem can be solved by using e-modules that incorporate contextual learning and teaching strategies. This study aims to compare the numeracy literacy of students who get direct instruction using school-provided teaching materials to that of students whose education is supplemented with e-modules based on content-based learning (CTL). Using a research strategy called the nonequivalent post test-only control group design, the study employed a quasi-experimental research approach. Students in the X grade at SMKN 1 Sijunjung were part in this research. There were two classes that participated in the study: X Accounting 2 and X Accounting 1. The former class employed CTL-based e-modules as a treatment, while the latter class used school-provided teaching materials for direct learning. The data analysis led the author to the conclusion that CTL-based e-modules improve students' numeracy literacy skills in class X at SMKN 1 Sijunjung compared to classes that depend on school-provided learning and teaching materials. These results show that students who use e-modules based on CTL have better numeracy literacy abilities.Keywords– Numeracy Literacy Skills, E-Module, Contextual Teaching and Learning